Exploring the diversity of plant model organisms - Plackett,ARG; Bowman,JL; Raissig,MT; Borrill,P; Merchant,SS; Qin,F; Yuen,ELH; Bozkurt,T; Xie,F (Developmental Cell, 2025)
Increasing plant genome research, together with advanced transformation technology, enables researchers to address their research questions more effectively in various models beyond Arabidopsis. In this collection of Voices, we asked researchers from different fields to discuss what model organisms they are using and why this helps answer their research questions.